Peningkatan Hasil Belajar Siswa Kelas IV SD Negeri 2 Bombas Melalui Penerapan Model Problem-Based Learning (PBL) - Hikmawati, Hikmawati; Zulfan, Zulfan; Raehani, Baiq Sri (Unram Journal of Community Service, 2023)
This community service activity aims to improve the learning outcomes of fourth grade students at SD Negeri 2 Bombas through the application of a problem-based learning (PBL) model. This activity took place at SD Negeri 2 Bombas with 12 participants. The activity was carried out in 2 meetings, namely on August 29 2022 and September 13 2022. The activity method includes 5 steps namely: 1) student orientation to the problem; 2) organizing students to study; 3) guiding individual and group investigations; 4) developing and presenting works; 5) analyze and evaluate the problem-solving process. Data on learning outcomes were obtained from giving cognitive tests at the end of the meeting. The results of the activity showed that student learning outcomes increased from the first meeting to the second meeting, namely from 30% of students achieving KKM at meeting 1 to 95% of students achieving KKM at the second meeting. Thus, the application of the PBL model has improved the learning outcomes of fourth grade students at SD Negeri Bombas. This PBL model can be used as a choice of innovative learning models to be implemented in elementary schools.